One new species of the Genus Scorpiops Peters, 1861 (Scorpiones: Euscorpiidae, Scorpiopinae) from Xizang, China - Di, Zhi-Yong; Zhu, Ming-Sheng (Zootaxa, 2009)
Scorpiops lhasa sp. n., from China Xizang (Lhasa) is described. S. lhasa is small in size with respect to other species in the genus; external trichobothria on the patella number 17 (5 eb, 2 esb, 2 em, 4 est, 4 et) and ventral trichobothria on the patella number 10 (11 rarely); pedipalp fingers in both sexes are curved; chela narrow and elongated, the ratio between length and width is above 2.6.